The relationship between technostress and job satisfaction among employees at Suruhanjaya Hak Asasi Manusia Malaysia (SUHAKAM), Kuala Lumpur / Syazana Mohd. Kamal - Mohd. Kamal, Syazana
The aim of the study was to identify the relationship of technostress and job satisfaction among the employees at Suruhanjaya Hak Asasi Manusia Malaysia (SUHAKAM). Technostress creator is one of the types of technostress’s component that has been chosen by the researcher. There were three technostress creators used in this study which are techno-overload, techno-uncertainty and techno-complexity. For this study, 90 questionnaires were distributed and only 84 questionnaires were returned and useable for further statistical analyses. Based on the research objectives and research questions that have been developed by the researcher, finding of the study showed that technostress contributes to job satisfaction among employees at Suruhanjaya Hak Asasi Manusia Malaysia (SUHAKAM). Furthermore, the finding also finds out the best way how to avoid technostress from happening at Suruhanjaya Hak Asasi Manusia Malaysia (SUHAKAM) and recommendation for future researchers. Besides, the researcher also has been discussed the conclusion and developed recommendation for employees and future researchers.